2017
DOI: 10.1177/0954411917713774
|View full text |Cite
|
Sign up to set email alerts
|

A combined experimental and finite element approach to analyse the fretting mechanism of the head–stem taper junction in total hip replacement

Abstract: Fretting corrosion at the taper interface of modular hip implants has been implicated as a possible cause of implant failure. This study was set up to gain more insight in the taper mechanics that lead to fretting corrosion. The objectives of this study therefore were (1) to select experimental loading conditions to reproduce clinically relevant fretting corrosion features observed in retrieved components, (2) to develop a finite element model consistent with the fretting experiments and (3) to apply more comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 28 publications
3
29
0
Order By: Relevance
“…The impaction forces generated by surgeons can vary significantly from approximately 300 N to an excess of 7500 N [15]. To date, the majority of studies [12,[16][17][18] investigating the influence of the assembly force have focused on the dissociation force as the metric to assess the performance of the taper. Assembly forces from 2 kN to 15 kN have been investigated and a linear relationship with the dissociation force has been reported [12,16].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The impaction forces generated by surgeons can vary significantly from approximately 300 N to an excess of 7500 N [15]. To date, the majority of studies [12,[16][17][18] investigating the influence of the assembly force have focused on the dissociation force as the metric to assess the performance of the taper. Assembly forces from 2 kN to 15 kN have been investigated and a linear relationship with the dissociation force has been reported [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Assembly forces from 2 kN to 15 kN have been investigated and a linear relationship with the dissociation force has been reported [12,16]. The dissociation force is always lower and varies between 42% [17] and 91% [18] of the assembly force. Rehmer et al [12] reported a similar linear relationship between the assembly force and the twist off torque.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations